Language, communication and intercultural understanding in peacekeeping operations - Najjah Salwa Abd Razak,; Ramli H Nik,; Kaseh Abu Bakar,; Mhd Faizal Mhd Ramli, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The deployment of the Malaysian Armed Forces (MAF) in the various operations since 1960 has clearly attained international recognition. However, the successful cases of Malaysian peacekeepers, specifically from the multidimensional perspective, have not been explored much even though their achievements are significant. This paper attempts to discuss the language and communication among Malaysian peacekeepers deployed in Congo and Somalia. The researchers analyse the intercultural understanding of Malaysian peacekeepers to attain the required mandate as stipulated in the United Nation Security Council. This is a multiple case study comprising of a series of interviews with selected participants deployed in Congo and Somalia. The data was transcribed verbatim and analysed thematically. This study highlights the importance of using appropriate ways of communication while dealing with the locals and peacekeepers. The peacekeeping operations with cultural identity factors made positive contributions to durable peace and stability under certain conditions. A number of recommendations are highlighted and it is hoped to assist the concerned parties in developing a concrete strategy.